Peningkatan Produktivitas Usaha Melalui Pemanfaatan Digital Marketing pada Emping Ketan Lumintu Kelurahan Sendangmulyo - Nurul Juwariyah; Nur Hasanah; Titi Purbo Sari (Institut Teknologi dan Bisnis Semarang, 2025)
One of the MSMEs in Sendangmulyo Village is the LUMINTU Sticky Rice UMKM in Sendangmulyo Village, Tembalang District, Semarang. MSMEs still use traditional marketing strategies so that marketing reach is still not wide enough and businesses are less developed. Likewise with the UMKM Emping Ketan Lumintu which until now has not been able to sell maximum products. MSME managers still have limited knowledge of using social media marketing as a marketing tool, conducting marketing and making transactions online. The target of this community service program is the Emping Ketan Lumintu MSME Business actors. The method used in carrying out this service activity is: Counseling and training activities for Emping Ketan Lumintu MSME Business Actors by utilizing the Digital platform to promote their business, so that it is hoped that visitors will increase and can increase sales turnover. In this way, it is hoped that partners will be able to carry out marketing activities better. The output that will be produced in this community service program activity is an increase in the ability to use digital platforms for business marketing by Emping Ketan Lumintu MSMEs using social media Instagram, improvements in product packaging, and the use of digital sales receipts. With this, it is hoped that it will support product sales using digital marketing tools.